Genomic organization of Hox and ParaHox clusters in the echinoderm, Acanthaster planci. Issue 12 (28th November 2014) - Baughman, Kenneth W.; McDougall, Carmel; Cummins, Scott F.; Hall, Mike; Degnan, Bernard M.; Satoh, Nori; Shoguchi, Eiichi
Summary The organization of echinoderm Hox clusters is of interest due to the role that Hox genes play in deuterostome development and body plan organization, and the unique gene order of the Hox complex in the sea urchin Strongylocentrotus purpuratus, which has been linked to the unique development of the axial region. Here, it has been reported that the Hox and ParaHox clusters of Acanthaster planci, a corallivorous starfish found in the Pacific and Indian oceans, generally resembles the chordate and hemichordate clusters. The A. planci Hox cluster shared with sea urchins the loss of one of the medial Hox genes, even‐skipped (Evx) at the anterior of the cluster, as well as organization of the posterior Hox genes. genesis 52:952–958, 2014. © 2014 Wiley Periodicals, Inc.